MedWet training sub-project: Application on test site Kerkini, Greece, Description of action and applicability of MedWet method for training. - Μ. Αναγνωστοπούλου; Κ. Σκορδάς; M. Anagnostopoulou; K. Skordas (Greek Biotope/Wetland Centre (EKBY), 1995)
MEDWET